Tecendo Papéis:viagem pelos saberes e práticas do ensino de arte - Evangelista, Maria do Socorro de Oliveira (2005)
Nowdays, recycling became a relevant social and educational aim among many other factors, which involve balance between man and nature. This study relates the experiences with the production of recycled handmade paper directed at the teaching in Universidade Federal do Rio Grande do Norte UFRN, and through workshops of carnauba recycled handcrafts papers as a pioneer activity accomplished at the Felix Rodrigues Foundation, in the city of Pendências, Açu Valley, Rio Grande do Norte. A bibliographic review was done about the history of handmade paper and a discussion about carnauba´s paper artistic possibilities in art-education. Analyses within the context of art teaching, accordingly to Ana Mae Barbosa´s triangle propose and, also, Buoro, Ostrower and Nachmanovitch´s pedagogy of art. It deals with a group of artisans in order to establish the nature of their relationship and the possibilities of achieving more ecological awareness. Finally, we intend to realize a dialogue with Morin and other authors